2022
DOI: 10.1038/s41598-022-04854-3
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput segmentation of unmyelinated axons by deep learning

Abstract: Axonal characterizations of connectomes in healthy and disease phenotypes are surprisingly incomplete and biased because unmyelinated axons, the most prevalent type of fibers in the nervous system, have largely been ignored as their quantitative assessment quickly becomes unmanageable as the number of axons increases. Herein, we introduce the first prototype of a high-throughput processing pipeline for automated segmentation of unmyelinated fibers. Our team has used transmission electron microscopy images of v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Deep-learning based algorithms have recently received attention in anatomically guided, medical image segmentation [44]. With regard to segmentation of anatomical features of nerves, deep-learning algorithms have been used on EM images [45], with regard to single fibers, and on ultrasound [46] and histological images [47], with regard to fascicles. To the best of our knowledge, this is the first use of convolutional neural networks, in particular mask-RCNN, on micro-CT and IHC data, to automatically segment and extract anatomical features at the fascicle and single fiber level.…”
Section: Discussionmentioning
confidence: 99%
“…Deep-learning based algorithms have recently received attention in anatomically guided, medical image segmentation [44]. With regard to segmentation of anatomical features of nerves, deep-learning algorithms have been used on EM images [45], with regard to single fibers, and on ultrasound [46] and histological images [47], with regard to fascicles. To the best of our knowledge, this is the first use of convolutional neural networks, in particular mask-RCNN, on micro-CT and IHC data, to automatically segment and extract anatomical features at the fascicle and single fiber level.…”
Section: Discussionmentioning
confidence: 99%
“…A list of the TEM images used in this study is shown in Table 1 . The protocols and techniques followed for nerve sample collection, processing, and imaging are documented in our previous work (Plebani et al, 2022 ). The data is publicly available via NIH-supported SPARC Pennsieve database (Havton et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The data is publicly available via NIH-supported SPARC Pennsieve database (Havton et al, 2022 ). Briefly, the unmyelinated axons in some of these TEM images were manually annotated and used as labeled data to train, validate, test, and evaluate an automated segmentation model based on the U-Net architecture (Ronneberger et al, 2015 ; Plebani et al, 2022 ). The segmentation model is a U-Net with four stages: the convolutional layers have a batch normalization layer followed by a ReLU activation layer, and the bottleneck stage has extra dropout layers between convolutions (Plebani et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations